Effects of 2,3-Dehydrosilybin and Its Galloyl Ester and Methyl Ether Derivatives on Human Umbilical Vein Endothelial Cells - Karas, Daniel; Gažák, Radek; Valentová, Kateřina; Chambers, Christopher S; Pivodová, Veronika; Biedermann, David; Křenková, Alena; Oborná, Ivana; Kuzma, Marek; Cvačka, Josef; Ulrichová, Jitka; Křen, Vladimír (Journal of natural products, 2016)
The effects in vitro of 2,3-dehydrosilybin and several galloyl esters and methyl ethers on the viability, proliferation, and migration of human umbilical vein endothelial cells (HUVECs) were evaluated. The monogalloyl esters were synthesized by a chemoselective esterification method or by Steglich esterification of suitably protected 2,3-dehydrosilybin (1) with protected gallic acid. 2,3-Dehydrosilybin (1) displayed more potent cytotoxic, antiproliferative, and antimigratory activities (IC50 12.0, 5.4, and 12.2 μM, respectively) than silybin. The methylated derivatives were less active, with the least potent being 3,7-di-O-methyl-2,3-dehydrosilybin (6). On the other hand, galloylation at C-7 OH and C-23 OH markedly increased the cytotoxicity and the effects on the proliferation and migration of HUVECs. The most active derivative was 7-O-galloyl-2,3-dehydrosilybin (13; IC50 value of 3.4, 1.6, and 4.7 μM in the cytotoxicity, inhibition of proliferation, and antimigratory assays, respectively). Overall, this preliminary structure-activity relationship study demonstrated the importance of a 2,3-double bond, a C-7 OH group, and a galloyl moiety in enhancing the activity of flavonolignans toward HUVECs.
Keywords: methylethery; vztahy mezi strukturou a aktivitou; Free Radical Scavengers; Humans; Structure-Activity Relationship; Silybin; Molecular Structure; scavengery volných radikálů; silymarin; Methyl Ethers; silibinin; Cell Survival; viabilita buněk; Human Umbilical Vein Endothelial Cells; endoteliální buňky pupečníkové žíly (lidské); lidé; Gallic Acid; kyselina gallová; molekulární struktura; Silymarin